2023
DOI: 10.5114/pg.2023.126043
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of adult type hypolactasia in patients with irritable bowel syndrome

Abstract: Introduction The incidence of lactose intolerance in irritable bowel syndrome (IBS) varies in the literature (27–72%). Primary adult lactase deficiency (adult type hypolactasia) is the most common type of primary enzyme deficiency. Complaints related to lactose intolerance may overlap with the symptoms of IBS. Aim To assess the prevalence of primary hypolactasia in patients with IBS. Material and methods The study included 56 patients with IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This is supported by the observation that more than 90% of the population in Scandinavian countries and the Netherlands, where the consumption of milk and its products is significant and long-lasting, have high lactase activity, in contrast to countries in Asia or most areas of Africa, where the frequency is about 10% [3,4]. In Europe, 2 polymorphisms of the LCT gene are responsible for reduced lactase production: C/T-13910 and G/A-220186 [5]. The TT and AA variants are dominant and determine the maintenance of lactase at high levels in adults, while the CC and GG variants are responsible for the formation of adult-type hypolactasia.…”
Section: Introductionmentioning
confidence: 84%
“…This is supported by the observation that more than 90% of the population in Scandinavian countries and the Netherlands, where the consumption of milk and its products is significant and long-lasting, have high lactase activity, in contrast to countries in Asia or most areas of Africa, where the frequency is about 10% [3,4]. In Europe, 2 polymorphisms of the LCT gene are responsible for reduced lactase production: C/T-13910 and G/A-220186 [5]. The TT and AA variants are dominant and determine the maintenance of lactase at high levels in adults, while the CC and GG variants are responsible for the formation of adult-type hypolactasia.…”
Section: Introductionmentioning
confidence: 84%
“…In a preliminary study, Kowalówka et al observed that young Polish adults with polymorphic variant −13910:C>T showed lower levels of vitamin D and calcium in LNP subjects compared with those with the −13910:T>T variant [117]. Moreover Dom żał-Magrowska et al, based on the results of the hydrogen breath test, observed no statistically significant differences between IBS patients who had the −13910:C>T and −22018:G>A polymorphism compared with the control group reporting hypolactasia [118].…”
Section: Lactase Deficiency and Lactose Intolerancementioning
confidence: 97%
“…In a preliminary study, Kowalówka et al observed that young Polish adults with polymorphic variant −13910:C>T showed lower levels of vitamin D and calcium in LNP subjects compared with those with the −13910:T>T variant [ 117 ]. Moreover Domżał-Magrowska et al, based on the results of the hydrogen breath test, observed no statistically significant differences between IBS patients who had the −13910:C>T and −22018:G>A polymorphism compared with the control group reporting hypolactasia [ 118 ].…”
Section: Lactase Deficiency and Lactose Intolerancementioning
confidence: 99%